Relationship of Diet and Lifestyle with Blood Sugar Levels in the Elderly with Diabetes Mellitus at Internist Room in Dr. Moedjito Dwidjosiswoyo Hospital of Jombang - Dina Aulia; Sentot Imam Suprapto; Soemarko Soemarko (Journal for Quality in Public Health, 2021)
The high number of people with diabetes mellitus is due to changes in people's lifestyle, knowledge level, and awareness to do early detection of diabetes mellitus disease that is lacking, lack of physical activity, traditional dietary arrangements containing carbohydrates and fiber from vegetables to diet to the west with a composition of foods that have too much protein, fat, salt, and sugar. The purpose of the study was to find out the relationship of diet and lifestyle with blood sugar levels in the elderly with diabetes mellitus. The design of this research is crossectional analytics. The variables of this study are diet and lifestyle as independent variables as well as blood sugar levels as dependent variables. The study population is all elderly diabetes mellitus patients (> 50 years old) and can communicate well in the poly disease in dr. Moerdjito Jombang Hospital as many as 145 patients. Samples were taken with simple random sampling techniques as many as 107 respondents. The data was collected with questionnaire instruments and processed using editing, coding, scoring and tabulating and tested with linear regression tests. The results of this study showed that partially and simultaneously (simultaneously) independent variables can affect the occurrence of dependent variables due to the value of < 0.05. This indicates that modern lifestyles that often consume fast food or fast food cause an increased risk of DM disease, including consuming beverages containing artificial sweeteners and excessive consumption of carbohydrates that can increase the risk of developing DM disease higher. Unhealthy diet that is by ignoring the type, amount and schedule or frequency of consumption that can cause metabolic disorders in the body, one of which is disorders in glucose metabolism.